The effect of Pistacia terebinthus extract on lipid peroxidation, glutathione,protein, and some enzyme activities in tissues of rats undergoing oxidative stress - Türkoğlu, Semra; Çelık, Sait; Keser, Serhat; Türkoğlu, İsmail; Ökkeş,; Yılmaz, Okkes; Yilmaz, (My University, 2017)
This study measures the effects of Pistacia terebinthus flower extract on the amounts of lipid peroxidation (LPO), total protein, glutathione, and enzyme activities in blood. It also measures the effects of the plant extract on glutathione peroxidase (GSH-Px) and superoxide dismutase (SOD) enzyme activities and it arrives at the conclusion that GSH-Px activity significantly increased in the Pistacia terebinthus-hydrogen peroxide group (P < 0.0001) and SOD activity meaningfully increased in the Pistacia terebinthus (P < 0.05) and Pistacia terebinthus-hydrogen peroxide (P < 0.0001) groups. It is also found that P. terebinthus extract has protective effects against LPO exerted in the kidney, brain, and lungs (P < 0.0001). The positive effects of P. terebinthus extract are also found on the levels of glutathione and total protein in all organs, except for the level of glutathione in the spleen and brain, and the increase of glutathione and total protein (P < 0.0001). These results are parallel to the effect of the extract used in this study on the LPO levels in tissues and they show that the plant species used in the study has positive effects on the activities of antioxidant molecules as well as protective effects against LPO.
Keywords: Biyoloji